Pollen distribution in the marine surface sediments of the mudbelt along the west coast of South Africa. (6th June 2016) - Zhao, Xueqin; Dupont, Lydie; Meadows, Michael E.; Wefer, Gerold
Abstract: The distribution of pollen in marine surface sediments offshore of the west coast of South Africa has been investigated to aid in the interpretation of marine pollen records of onshore vegetation changes. A transect of sediment surface pollen samples retrieved from the Namaqualand mudbelt from just south of the Orange River mouth (29°S) to St Helena Bay (33°S) indicates distinctive pollen spectra reflecting vegetation communities on the adjacent continent. Pollen concentration increases southwards, partly in relation to greater pollen productivity due to higher biomass and density of fynbos vegetation and of sedimentary processes and low pollen concentrations consequent to dilution with silt and clay from the Orange River. The distribution of specific pollen taxa suggests that the Orange River is a major contributor of pollen to the northern mudbelt declining southwards, while the pollen distribution in the central mudbelt is largely attributable to seasonal inputs of pollen from offshore berg winds and local ephemeral Namaqualand rivers. The typical fynbos elements dominate in the southern mudbelt indicating a pollen source mainly in the fynbos vegetation types. These conclusions support a companion analysis of fossil pollen records of two marine sediment cores from the northern and southern mudbelt respectively. This study demonstrates that pollen records from marine sediment cores in the Namaqualand mudbelt have the potential to be a tool to reconstruct palaeovegetation on the adjacent continent. However, to better reconstruct the palaeoclimate of South Africa and fully understand the relations between terrestrial and marine deposits, more marine surface sediments along the western coast of South Africa as well as more terrestrial surface sediments need to be studied.